2016
DOI: 10.18280/ijht.340307
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Simulation for Heatline Visualization of Natural Convective Flow and Heat Transfer inside a Prismatic Enclosure

Abstract: Finite element simulation is performed visualizing heat flow through heatlines for a free convection flow and heat transfer in an air-filled prismatic enclosure. This configuration has applications in collecting solar energy in attic spaces of greenhouses and buildings having pitched roofs. The top inclined walls of the enclosure are considered at constant low temperature, two vertical walls are adiabatic whereas the bottom wall is heated isothermally as well as non-isothermally. The Galerkin weighted residual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The understanding of thermal transport in complex geometries with discrete heat sources is of major importance. The applications include disposal of nuclear wastes, electronic circuits, geothermal areas, food processing industries and cooling of electronic components [1][2][3][4][5]. A thorough understanding of thermal transport in complex geometries with discrete heat source is essential in the design of above equipment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The understanding of thermal transport in complex geometries with discrete heat sources is of major importance. The applications include disposal of nuclear wastes, electronic circuits, geothermal areas, food processing industries and cooling of electronic components [1][2][3][4][5]. A thorough understanding of thermal transport in complex geometries with discrete heat source is essential in the design of above equipment.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the enhancement of heat transfer rate depended on the increment of solid wall thickness. Alam et al investigated the thermal transport in a prismatic cavity which is filled with air [5]. It was observed that the heatlines are normal to the isotherms in conduction dominant regime.…”
Section: Introductionmentioning
confidence: 99%
“…This convection is generated by buoyancy due to simultaneous temperature and concentration gradients. A sizable amount of research interests has been addressed on this subject (Mirabedin, 2016;Alam et al 2016;Bennacer et al 2001;Béghein et al 1992;Han et al 1992;Wee et al 1989;Chen et al 2011;Ghachem et al 2012;Tofaneli et al 2009;Costa, 2004). The outcome shows the occurrence of an oscillatory flow, provoked by the equilibrium between thermal and compositional forces, for a buoyancy number near the unity.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 is the analyzed heat exchanger spoiler model, it is a further improvement on the basis of predecessors summarized. The improved spirality inserted piece manufacturing process is much easier, not only reduces the cost, improves the production efficiency, but also improves the heat transfer efficiency [6]. Since the large helical curved surface including the entire tube bundle, which is difficult to manufacture, is simplified into a spiral insert which can be easily manufactured and embedded in each tube.…”
Section: Introductionmentioning
confidence: 99%